Clinical and genetic characteristics and natural history of Finnish families with familial exudative vitreoretinopathy due to pathogenic FZD4 variants - Lähteenoja, Laura (Wiley-Blackwell, 2025)
Purpose: To report clinical and genetic characteristics of familial exudative vitreoretinopathy (FEVR) in the Finnish population.
Methods: Detailed clinical and genetic data of 35 individuals with heterozygous pathogenic variants in FZD4 were gathered and analysed.
Results: Thirty-two individuals with FZD4 c.313A>G variant and three individuals with FZD4 c.40_49del were included in the study. The clinical phenotype was variable even among family members with the same FZD4 variant. Only 34% (N = 12/35) of variant-positive individuals had been clinically diagnosed with FEVR. The median age of the onset of symptoms was 2.3 years, ranging between 0 to 25 years. Median visual acuity was 0.1 logMAR (0.8 Snellen decimal), ranging between light perception and -0.1 logMAR (1.25 Snellen decimal). Most (N = 33/35, 94%) were classified as not visually impaired. Despite unilateral visual loss present in some, they did not meet the criteria of visual impairment according to the WHO classification. Two study patients (N = 2/35, 6%) had severe visual impairment. The most common FEVR stage in study patient's eyes (N = 28/70 eyes, 40%) was FEVR stage 1, that is, avascular periphery or abnormal vascularisation. Most of FZD4-variant-positive study patient's eyes (N = 31/50 eyes, 62%) were myopic. Two individuals presented with persistent hyperplastic primary vitreous expanding the phenotypic spectrum of FEVR. Shared haplotypes extending approximately 0.9 Mb around the recurrent FZD4 c.313A>G variant were identified.
Conclusion: Most study patients were unaffected or had mild clinical manifestations by FEVR. Myopia seemed to be overly common in FZD4-variant-positive individuals.